sqrt(x+1)+sqrt(x+2)=3

Simple and best practice solution for sqrt(x+1)+sqrt(x+2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(x+1)+sqrt(x+2)=3 equation:


Simplifying
sqrt(x + 1) + sqrt(x + 2) = 3

Reorder the terms:
qrst(1 + x) + sqrt(x + 2) = 3
(1 * qrst + x * qrst) + sqrt(x + 2) = 3
(1qrst + qrstx) + sqrt(x + 2) = 3

Reorder the terms:
1qrst + qrstx + qrst(2 + x) = 3
1qrst + qrstx + (2 * qrst + x * qrst) = 3
1qrst + qrstx + (2qrst + qrstx) = 3

Reorder the terms:
1qrst + 2qrst + qrstx + qrstx = 3

Combine like terms: 1qrst + 2qrst = 3qrst
3qrst + qrstx + qrstx = 3

Combine like terms: qrstx + qrstx = 2qrstx
3qrst + 2qrstx = 3

Solving
3qrst + 2qrstx = 3

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Reorder the terms:
-3 + 3qrst + 2qrstx = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + 3qrst + 2qrstx = 0

The solution to this equation could not be determined.

See similar equations:

| 3(x+1)+1=2(x-1)+3 | | 9x+2=7x-10 | | 6x-4-4x-3= | | 19=4(w-2)+5w | | 2(x-5)+20=40 | | 6z-14=-18 | | x=0.6410256410y | | 2(5m-6)-12-15=-9 | | 17=-5v+8(v+4) | | 5/57.25 | | 7x(4x+2)=5 | | 2x+3(3x+17)=183 | | 3+6+x=5+4 | | 5v+3v-18=-74 | | 2x-5=3+2 | | 8p+4=-21 | | 10(x-1)+(4x+14)+22=82 | | 3x-2/4=-3 | | 1.56x=y | | 3x+4(x-7)=14 | | 15-14+x=9 | | x-4+1=7 | | y=1.56x | | -6x-8(-2+6x)=178 | | 16x^2-8x-7=0 | | y=1.56 | | -2x+16+6x=44 | | x-4+1=8 | | x-4/16=5/8 | | 6a+7n-3n+a= | | 5/6x=7/8 | | x(x+20)=180 |

Equations solver categories